Spousal Labor Supply: Decoupling Gender Norms and Earning Status - Elliott Isaac (Institute of Labor Economics (IZA), 2024)
Many household labor supply models divide couples by sex and identify separate male and female labor supply parameters. However, institutional factors in the labor market suggest that men are more likely to be primary earners in their household, meaning that intra-household gender gaps in labor supply may reflect both gender norms and earning status. I use a novel identification approach to disentangle the role of gender norms in intra-household labor supply by estimating collective labor supply models for different- and same-sex married couples. Among childless couples, I present point estimates and construct unified bounds showing that gender norms significantly increase the weight placed on women's utility by 1.1–5.1%, leading to lower labor supply. A back-of-the-envelope calculation suggests that the effect of gender norms on married, childless couples' labor supply is equivalent to a substantial widening of the gender wage gap.
Keywords: J16; D13; J22; H24; 330; collective model; labor supply; gender norms